2021
DOI: 10.1371/journal.pone.0254696
|View full text |Cite
|
Sign up to set email alerts
|

Home delivery practice and its predictors in South Ethiopia

Abstract: Background Institutional delivery is one of the key interventions to reduce maternal death. It ensures safe birth, reduces both actual and potential complications, and decreases maternal and newborn death. However, a significant proportion of deliveries in developing countries like Ethiopia are home deliveries and are not attended by skilled birth attendants. We investigated the prevalence and determinants of home delivery in three districts in Sidama administration, Southern Ethiopia. Methods Between 15–29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
5
2
Order By: Relevance
“…Our study also found that the prevalence of home delivery was 31.88% (95% CI: 27.42, 36.61%). This result was higher than previous reports in Ethiopia (13,15,32). This might be due to the difference in the study setting; the previous studies were institutional based while our study was community-based.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Our study also found that the prevalence of home delivery was 31.88% (95% CI: 27.42, 36.61%). This result was higher than previous reports in Ethiopia (13,15,32). This might be due to the difference in the study setting; the previous studies were institutional based while our study was community-based.…”
Section: Discussioncontrasting
confidence: 76%
“…Similarly, women with no formal education were more likely to practice food taboos, home delivery, and pre-lacteal feeding than women with primary and above education. This association was documented elsewhere (5,10,13,15,29), and could be related to the lack of awareness about the harmful effect of cultural malpractices on the health of the mother and her offspring among women without formal education.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Rural residence, distance to health facility, low antenatal care coverage, and economic status are common societal factors. Also, low education, not planning for place birth, and unknown due date [10][11][12] were significant predictors. Moreover, socio-cultural factors such as assuming labor and delivery as a natural process, presence of enjoyable rituals during and after delivery, perceived friendly care by traditional attendants, and unavailability, inaccessibility, and perceived poor quality of modern services were qualitatively extracted factors [13][14][15] for home delivery in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Most rural women in Sidama Region (formerly known as Sidama Zone) face difficulty in accessing distant health facilities to use maternal health services [ 18 , 19 ]. In addition, poor landscape and topography make institutional delivery less reliable in this region.…”
Section: Introductionmentioning
confidence: 99%